Patterns of change in coral reef communities of a remote Maldivian atoll revisited after eleven years - Zampa, Greta; Azzola, Annalisa; Bianchi, Carlo Nike; Morri, Carla; Oprandi, Alice; Montefalcone, Monica (PeerJ, 2023)
Coral reefs are exposed worldwide to several global and local human pressures including climate change and coastal development. Assessing the effects of such pressures on coral reef communities and the changes they undergo over time is mandatory to understand their possible future trends. Nonetheless, some coral reefs receive no or little scientific attention, as in the case of Huvadhoo Atoll that is an under-studied region in the southernmost area of the Maldives (Indian Ocean). This study analyzes the changes occurring over time in eight coral reefs (four inner reefs within the atoll lagoon and four outer reefs on the ocean side) at Huvadhoo Atoll, firstly surveyed in 2009 and revisited in 2020 using the same field methods. The cover of 23 morphological benthic descriptors (including different growth forms of Acropora) was taken into account and then grouped into three categories (i.e., hard coral, other benthic taxa and abiotic descriptors) to analyze the change in the composition of the coral reef community. Significant changes (e.g., increase in hard coral cover and decrease in abiotic descriptors) were observed in the inner reefs as compared to the outer reefs, which showed less variability. A significant decrease in tabular Acropora cover was observed in both inner and outer reefs, with possible negative effects on reef complexity and functioning. By comparing two time periods and two reef types, this study provides novel information on the change over time in the community composition of Maldivian coral reefs.
Keywords: Benthic community composition; Remote atoll; Change over time; Coral reefs; Maldives; Indian Ocean